Postpartum Eclampsia -Anaesthetic Challenges - Kiran Sharma; Bhanu Prakash (Academia Anesthesiologica International, 2019)
Managing a patient with eclampsia for caesarean section is an anaesthetic challenge. Most of the time the patients present for emergency caesarean section. We are reporting two case reports of eclampsia.  First patient with eclampsia was referred from primary health centre. Cesarean section was uneventful under spinal anesthesia but patient had multiple seizures in the postoperative period.  Patient was managed in the ICU and was discharged on the 7th postoperative period.  Second patient was given general anesthesia and was electively ventilated in the ICU.